The Impact of Corporate Governance on Accounting Conservatism in the Financial Statements of Justice Shareholders - Al-Abedi, Thamer Kadhim; Hasen, Ali Mahmood; Mohaisen, Hussein Ali; Flayyih, Hakeem Hammood (CENTRAL ASIA AND THE CAUCASUS, 2022)
Conservatism creates a system that prevents overpayments to managers and reduces the conflict between the interests of shareholders and managers. On the other hand, conservatism over corporate governance, while reducing opportunistic management payments, causes the manager to report losses from the sale of assets and also stops operations, and prevents the manager from continuing to invest in projects with negative net worth. Therefore, the aim of this study was to determine the impact of corporate governance on accounting conservatism in the financial reports of justice shareholders. The statistical population of the present study is the companies listed on the Iraq Justice Stock Exchange and using the elimination sampling method, 30 companies were selected as the research sample during the period 2013 to 2020. Using multivariate regression models, the results indicate that there is no relationship between corporate governance mechanisms and conservatism in financial reporting.